Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes) - Armbruster, Jonathan W.; Werneke, David C. (Zootaxa, 2005)
Peckoltia cavatica is described as a new species and P. braueri is redescribed. Peckoltia cavatica and P. braueri differ from all other Peckoltia by having distal orange bands on the dorsal and caudal fins when alive and by having the plates and bones of the head and nape outlined in black. Peckoltia cavatica is found in the Essequibo River basin, and P. braueri is found in the Takutu River basin. The species differ in that P. cavatica has weaker dorsal saddles, the plates and bones of the head and nape are completely outlined in black (vs. partially outlined in P. braueri), lacks vermiculate lines on the pterotic-supracleithrum, lacks at least one, broken band in the caudal fin, and has wider orange bands.